Wadiah In The Perspective Of Islamic Law And Its Application In Sharia Banking - Ahmad Ibrohim (Values: Jurnal Kajian Islam Multidisiplin, 2025)
Wadi'ah is practiced in banks that use the sharia system, such as Bank Muamalat Indonesia (BMI, Bank Islam). Bank Muamalat Indonesia defines wadi'ah as a pure deposit which, with the permission of the depositor, can be used by the bank. The concept of wadi'ah developed by BMI is wadi'ah yad ad dhamanah (entrustment regarding the risk of compensation). Therefore, wadi'ah which fiqh experts define as yad Al-Amanah (pure deposit without compensation) is modified in the form of yad ad dhamanah (with risk of compensation). The consequence is that if BMI manages the money and makes a profit, then all the profits belong to the bank. Cumulatively, wadi'ah has two meanings, the first is a statement from someone who has given power of attorney or delegated to another party to look after or look after his property; secondly, an asset that someone entrusts to another party is maintained or guarded.